Developing multilingual pedagogies and research through language study and reflection. Issue 1 (2nd January 2018) - Catalano, Theresa; Shende, Madhur; Suh, Emily K.
ABSTRACT: Globalisation and increased transnational migration underscore the need for educational responses to multilingualism and multilingual discourses. One way to heighten awareness of multilingual pedagogies (while simultaneously providing data for multilingual research) is the use of reflective language study and journaling by language educators/researchers. The purpose of this collaborative autoethnography, which focuses on the United States, is to demonstrate how this can be accomplished in language teacher education courses to help raise awareness and interest of how to capitalise on students' linguistic and cultural resources. Data for this study included three participant/researcher journals and observational notes from collaborative discussions among researcher/participants about the lived experiences of multilingual language educators as they studied a new language and wrote about their experiences. Findings reveal possibilities for future research in cross-linguistic transfer as well as the teaching of multilingual pedagogies and issues of social justice as it relates to multilingual education.